Ethnobotanical study of medicinal plants in the coastal districts of Odisha - S.S. Lenka and N.K. Dhal, S.C. Sahu*, S.K. Pattnaik, S. L. Sahoo, (Current Botany, 2011)
Ethnobotanical study was carried out in the coastal districts of Odisha during 2010-2011 to document the medicinal utility of plants. The present paper deals with traditional uses of 46 plant species belonging to 44 genera and 32 families along with correct botanical identification, local names, parts used and mode of administration in respect to different diseases.Ã‚Â  The documented ethnomedicinal plants are mostly used to cure skin diseases, diarrhoea, jaundice, piles and urinary troubles.